2011
DOI: 10.1111/j.1445-2197.2011.05858.x
|View full text |Cite
|
Sign up to set email alerts
|

Sphenoid ridge meningioma presenting as ischemia stroke

Abstract: The World Health Organization classification differentiates ependymomas into four types: papillary ependymoma is a grade II variant. Prognostic factors and management of these tumours are still controversial because of the rarity and the heterogeneity of series reported in the literature. In 2007, Metellus et al. emphasized that in association with Karnofsky performance status and extent of surgery, histological grade is a major prognostic factor in adult intracranial ependymomas. 3 We present a case of low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…2 Shuaib et al reported a case of a patient with clinical presentation of a transient ischaemic attack and initially negative computed tomography scan, which revealed to be a meningioma in a later scan. 3 In conclusion, we agree with Cheng et al 1 that in strokesuspected patients, the possibility of a meningioma should be considered in the differential diagnosis.…”
Section: Meningioma Compressing the Premotor Cortex Misdiagnosed For supporting
confidence: 91%
See 2 more Smart Citations
“…2 Shuaib et al reported a case of a patient with clinical presentation of a transient ischaemic attack and initially negative computed tomography scan, which revealed to be a meningioma in a later scan. 3 In conclusion, we agree with Cheng et al 1 that in strokesuspected patients, the possibility of a meningioma should be considered in the differential diagnosis.…”
Section: Meningioma Compressing the Premotor Cortex Misdiagnosed For supporting
confidence: 91%
“…1 We would like to comment on a similar case from our experience where a meningioma compressing the premotor cortex was misdiagnosed for a stroke. 1 They interestingly described a sphenoid ridge meningioma case presenting as ischaemia stroke.…”
Section: Meningioma Compressing the Premotor Cortex Misdiagnosed For mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the incidence of complete cerebral infarction resulting from arterial occlusion or obstruction related to meningioma is extremely rare4,9,13,15). We have summarized the reported cases from English literature of complete cerebral infarction caused by a meningioma in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Transient ischemic attack is a known complication of skull base meningioma. However, acute cerebral infarction, resulting from intracranial arterial occlusion or obstruction related to meningioma is extremely rare4,9,13,15). Here, the authors report a case of sphenoid ridge meningioma presenting with acute cerebral infarction caused by middle cerebral artery (MCA) compression.…”
Section: Introductionmentioning
confidence: 97%